2022
DOI: 10.1371/journal.pdig.0000002
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-based interventions for mental health: A systematic meta-review of 14 meta-analyses of randomized controlled trials

Abstract: Mobile phone-based interventions have been proposed as a means for reducing the burden of disease associated with mental illness. While numerous randomized controlled trials and meta-analyses have investigated this possibility, evidence remains unclear. We conducted a systematic meta-review of meta-analyses examining mobile phone-based interventions tested in randomized controlled trials. We synthesized results from 14 meta-analyses representing 145 randomized controlled trials and 47,940 participants. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
116
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 66 publications
5
116
0
3
Order By: Relevance
“…This suggests the presence of sampling bias and therefore limits the generalizability of our results to the population. It also informs us that this may be the population that is most interested, motivated for and in need of mHealth support [ 35 ]. Whether indeed the Grow It!…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the presence of sampling bias and therefore limits the generalizability of our results to the population. It also informs us that this may be the population that is most interested, motivated for and in need of mHealth support [ 35 ]. Whether indeed the Grow It!…”
Section: Discussionmentioning
confidence: 99%
“…For many, therapists trained in DBT are simply not accessible. E-mental health, which provides mental health services through digital information and communication technologies (e.g., smartphone applications, the Internet), has been widely used to promote mental health in the past decade [ 10 , 11 ]. E-mental health has the potential to increase cost-effectiveness [ 12 ], expand access to mental health resources [ 13 ], reduce the stigma associated with seeking traditional psychotherapy [ 14 ], and provide personalized psychological services [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pooled effect size for the four comparisons between smartphone intervention + standard intervention vs. the standard intervention-only arm was g=0.26 (95% CI: -0.09 to 0.61). A recent metareview of meta-analyses of digital interventions (19) reported that smartphone interventions for depression did not differ significantly…when tested as an adjunct to treatment (d = 0.26 [21]). The findings in the present report suggest that the effect size observed for Cue, when added to standard outpatient care in an academic department of psychiatry for patients with major depression, is substantially larger than those reported to date.…”
Section: Discussionmentioning
confidence: 99%